Hot Melt Extruded Amorphous Solid Dispersion of Posaconazole with Improved Bioavailability: Investigating Drug-Polymer Miscibility with Advanced Characterisation - Fule, Ritesh (Hindawi Publishing Corporation, 2014)
Invasive antifungal infections are reasons for morbidity and mortality in immunogenic patients worldwide. Posaconazole is a most promising antifungal agent against all types of invasive infections with high % of cure rate. The marketed suspension formulation has low bioavailability and is needed to be taken with food. In this paper, PCZ hot melt extruded amorphous solid dispersion (SD) with immediate release and improved bioavailability was prepared using Soluplus (Sol) as primary carrier for solubilization. Surfactants such as PEG 400, Lutrol F27, Lutrol F68, and TPGS are also used in combination with Soluplus to improve the physicochemical performance of the formulation when it comes in contact with GI (gastrointestinal) fluid. Drug-polymer miscibility of SD was investigated using advanced techniques. In the in vivo study, the AUC((0–72)) and C(max) of PCZ/Soluplus were 11.5 and 11.74 time higher than those of pure PCZ. The formulation of the extrudate SD had an AUC((0–72)) and C(max) higher than those with the commercial capsule (Noxafil). Molecular dynamic (MD) simulation studies were carried out using in silico molecular modelling to understand the drug-polymer intermolecular behaviour. The results of this research ensure enhanced dissolution and bioavailability of the solid dispersion of PCZ prepared by HME compared with the PCZ suspension.